Avaliação termo-econômica de sistemas de ciclo rankine orgânico para recuperação de calor residual e repotenciação de uma termelétrica à biogás de aterro sanitário - Loyola, Lucas Rodrigues (2023)
Faced with the importance of producing additional energy with reduced environmental impacts to satisfy the growing demand for energy, the term Waste Heat Recovery (WHR) arises, which is basically the recovery of thermal waste by transforming it into useful energy. Thermal power plants that operate with internal combustion engines reject considerable amounts of heat through the exhaust gas and cooling systems. Among the various technologies for energy recovery, an attractive alternative, which has been widely studied in recent years, is the use of Organic Rankine Cycle (ORC), which aims to increase energy efficiency without the additional use of fuel. However, for the implementation of this technology an economic evaluation must be done to understand its viability. This work has as a case study the thermoelectric plant of the Urban Solid Waste (USW) valorization company, Marca Ambiental. Starting from nominal data, a thermodynamic analysis of the Generating Units (GUs) that compose the plant is performed, including balances of mass, energy and exergy. Next, two organic Rankine cycles are modeled for the recovery of each residual heat source: exhaust gases and engine cooling water, using EES and IPSEpro softwares. The economic analysis is based on a method of parametric equations for determining the costs of each equipment, obtaining the total value of the initial investment in each plant modeled and with this are performed calculations of economic viability indicators: PayBack (simple and discounted), Net Present Value (NPV) and Internal Rate of Return (IRR). The main contribution of this work is to perform a preliminary study of the possibility of repowering a biogas thermal power plant. The results show that, of the modeled cycles, only the one that uses the heat from the exhaust gases is economically feasible, and can generate an increase of almost 13% in the electric power generated in the thermoelectric plant and presenting a discounted payback of about 6 years.